SEASONAL OCCURRENCE OF THE COTTON SEED BUG OXYCARENUS HYALINIPENNIS COSTA ON HIBISCUS SABDARRIFFA L. IN BAGHDAD.: SEASONAL OCCURRENCE OF THE COTTON SEED BUG OXYCARENUS HYALINIPENNIS COSTA ON HIBISCUS SABDARRIFFA L. IN BAGHDAD. (Iraqi Journal of Market Research and Consumer Protection, 2026)
The field study was conducted in Abu Ghraib / Baghdad in the Agricultural Protection Department of the Ministry of Agriculture, for the 2023 agricultural season. Seeds of Hibiscus sabdarriffa L., of the two varieties, red and dark red, were planted for the purpose of studying the population density and seasonal presence of the cotton seed bug Oxycarenus hyalinipennis on the plant. The results showed that the first appearance of adults was in the third week of July, on the red and dark red varieties, at a rate of 4 and 5.5 adults/one sweep on sweeping net and 1.13 and 1.63 adults/one yellow sticky trap, respectively. The numbers of adults reached their peak on the eighteenth of July. During the month of December, there were an average of 12.44 and 15.88 adults/one sweep on sweeping net, 2.38 and 2.63 adults/yellow sticky trap, and 1.85 and 2.3 adults/fruit, espectively, also for the red and dark red varieties.As for eggs and nymphs, they first appeared in the first and second week of October, at a rate of 1.61 and 1.74 eggs/one fruit, and 1.3 and 1.81 nymphs/one fruit on both the red and dark red varieties, respectively, and their peak was also on the eighteenth of the month. December, at a rate of 5.9 and 8.19 eggs/fruit and 5.55 and 7.76 nymphs/fruit, respectively, for the two varieties.